Experiencing Finnish Lapland: Design for Sustainability Through Cultural Communication in Tourism - Li, Yiling (2021)
Tourism, as an important domestic economy booster, has been heavily hit by the COVID-19 pandemic and severely declined. Governments are rethinking tourism for future new opportunities. Previous research has shown that large development scale of tourism is not conducive to sustainability, nevertheless, researchers have also found that managing tourists’ behavior can reduce the adverse effects, while other studies are proposing the effectiveness of environmental education on sustainability. However, little attention has been paid to the combination of environmental education and tourist management for sustainability purpose. This study aims to explore the potential of sustainability-oriented design through cultural communication in tourism. No matter what method is used to communicate sustainability, this research believes that the impacts of communication should seek to be sustainable and far-reaching, and more importantly to be applied in reality to present its value. To achieve the goal, this study takes Finnish Lapland as a practical entry point, follows service design thinking and takes ethnography as the research strategy, conducting qualitative research through semi-structured interviews, field studies, and workshops. The data from 57 stakeholders have been collected to quest opportunities and needs, based on which, a design outcome was produced as feedback for iterate. The findings show that sensory design can prolong the impact of sustainability, and the application of environmental education as a cultural content can meet the needs of stakeholders while contributing to sustainability. Furthermore, online sales may provide alternative options to alleviate COVID-19 impact on tourism industry and to build economic resilience and consumer confidence. The results show considerable potential in cultural communication for sustainability in tourism, which offers directions for future research in the area.